Analisis Solvabilitas, Profitabilitas, Likuiditas dan Pengaruhnya terhadap Financial Distress dengan Good Corporate Governance Sebagai Variable Moderasi - Albertin Yunita Nawangsari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the impact of solvency, profitability, and liquidity on financial distress, with good corporate governance as a moderating variable. The research employs a quantitative approach with moderation regression analysis. The results indicate that solvency, profitability, and liquidity have a significant negative effect on financial distress, meaning that the better a company's financial condition in these aspects, the lower the potential for financial difficulties. Additionally, good corporate governance is proven to moderate the effect of solvency, profitability, and liquidity on financial distress, indicating that the application of good governance strengthens the negative relationship between these financial indicators and financial distress. These findings highlight the importance of corporate management in maintaining financial health and applying good corporate governance principles to minimize the risk of financial distress.